2009
DOI: 10.1007/s10867-009-9127-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Analysis of the Dynamics of DNA Breathing

Abstract: The base pairs that encode the genetic information in DNA show large amplitude localized excitations called DNA breathing. We discuss the experimental observations of this phenomenon and its theoretical analysis. Starting from a model introduced to study the thermal denaturation of DNA, we show that it can qualitatively describe DNA breathing but is quantitatively not satisfactory. We show how the model can be modified to be quantitatively correct. This defines a nonlinear lattice model, which is interesting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 22 publications
1
88
0
Order By: Relevance
“…As the energy per hydrogen bond is about 15meV , I set for AT − and GC− bases respectively D AT = 30meV and D GC = 45meV . ATbase pairs have larger displacements than GC-base pairs, then the inverse lengths are taken as a AT = 4.2Å −1 and a GC = 5Å −1 while slightly different values can be found in the literature [47,48]. Note that the plateau in V M (y n ) has a relevant physical implication: once all base pair displacements are larger than a −1…”
Section: Hamiltonian Modelmentioning
confidence: 99%
“…As the energy per hydrogen bond is about 15meV , I set for AT − and GC− bases respectively D AT = 30meV and D GC = 45meV . ATbase pairs have larger displacements than GC-base pairs, then the inverse lengths are taken as a AT = 4.2Å −1 and a GC = 5Å −1 while slightly different values can be found in the literature [47,48]. Note that the plateau in V M (y n ) has a relevant physical implication: once all base pair displacements are larger than a −1…”
Section: Hamiltonian Modelmentioning
confidence: 99%
“…For the equilibrium calculations, we used PBD model and found the denaturation point in thermal as well as in constant force ensembles. For the homogeneous chain, we found that there is a segment (4)(5)(6)(7)(8)(9)(10)(11)(12) of the chain where T m is unaffected by the location of the defect in the chain. In case of heterogeneous chain, there is no plateau but it matters on a location whether there is an AT pair or a GC pair.…”
Section: Discussionmentioning
confidence: 89%
“…Although the model ignores the helicoidal structure of the dsDNA molecule, it has enough details to analyze mechanical behavior at the few angstrom scale relevant to molecular-biological events [10]. The Hamiltonian for the considered system of N base pairs unit is written as,…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The PB model and some variations [5][6][7] have been used to study the dynamics [8][9][10] and the thermodynamics [11][12][13] of DNA. From the dynamical point of view, there are studies about localized energy modes [14] that were identified as precursors of the denaturation and transcription process.…”
Section: Introductionmentioning
confidence: 99%